If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2/3x+1/6=3/4x+1
We move all terms to the left:
2/3x+1/6-(3/4x+1)=0
Domain of the equation: 3x!=0
x!=0/3
x!=0
x∈R
Domain of the equation: 4x+1)!=0We get rid of parentheses
x∈R
2/3x-3/4x-1+1/6=0
We calculate fractions
48x^2/432x^2+288x/432x^2+(-324x)/432x^2-1=0
We multiply all the terms by the denominator
48x^2+288x+(-324x)-1*432x^2=0
Wy multiply elements
48x^2-432x^2+288x+(-324x)=0
We get rid of parentheses
48x^2-432x^2+288x-324x=0
We add all the numbers together, and all the variables
-384x^2-36x=0
a = -384; b = -36; c = 0;
Δ = b2-4ac
Δ = -362-4·(-384)·0
Δ = 1296
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{1296}=36$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-36)-36}{2*-384}=\frac{0}{-768} =0 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-36)+36}{2*-384}=\frac{72}{-768} =-3/32 $
| 3-7*(3+5x)=-18 | | .58n=7.54 | | 7x-(2x+39)=1 | | x^2+27/X=0 | | 4y12=-4 | | 12.52+.9x=13.27+.13x | | 14=m/10=24 | | 7(x-1)+2X=6(x-8)-1 | | 104=1/2h(8+5) | | -7(d-3)=21 | | 7(x-1)=2X=6(x-8)-1 | | 3(4g+6)=2(6g+) | | 2x+(4x+16)=16 | | V=x(24-2x)(16-2x)(4) | | 11=c/5=8 | | 8x+7x-60=80-5x | | 2b^2+98=0 | | 4x+6x-16=80-6x | | 8x(2+3)=2x(8+3) | | 2x+4=24−3x | | 5m+12-2m=14 | | -121=5x-6x | | 9-z=-5-z | | 3x-5+6x=49 | | 11/20=x/30 | | 8x=50−2x | | 10/20=x/30 | | -7+x-4=9 | | 4x+4=-8-2x | | 1.5b+6+0.5b=15+2b | | 9n=1 | | (4x-3)+(x+8)=(2x-5) |